Inhibitory effect of endostatin gene therapy combined with phosphorus-32 colloid on tumour growth in Wistar rats. Issue 3 (30th June 2016) - Gao, Huiqi; Zhu, Jing; Li, Yong; Fu, Peng; Shen, Baozhong
Abstract : Eighty healthy male Wistar rats, aged 5 weeks, weighing 100–120 g, were utilized for establishing tumour-bearing models by immediate Walker-256 cancerous ascites injection and randomly divided to four groups ( n =20) treated with 0.2 ml solution containing saline, 32 P-colloid (0.3 mCi), endostatin gene (20 μg), endostatin gene combined with colloid 32 P. The effect of endostatin combined with a small dose of 32 P-colloidal on tumour growth in vivo was evaluated and the potential mechanism underlying the combined therapy was explored. We found that 32 P-colloid combined with endostatin exhibited higher inhibitory effect upon tumour growth compared with application of 32 P-colloid or endostatin alone, although three therapies all significantly inhibited tumour growth compared with saline control group. The higher inhibitory effect of 32 P-colloid combined with endostatin upon tumour growth might be attributed to a synergistic effect of inhibiting angiogenesis by endostatin and inducing apoptosis by 32 P-colloid, as demonstrated by microvessel density (MVD) and apoptotic index (AI) measurement. Combined therapy of 32 P-colloid and endostatin probably serves as a novel and efficacious therapy of tumour growth.